Prevalence of Protein-Energy Malnutrition among Under-five Dalit Children in Selected VDCs of Morang District - Gachhadar, Rashmi; Shah, Tara; Yadav, Birendra Kumar; Shrestha, Sharmila (Journal of Karnali Academy of Health Sciences, 2021)
Background: The degree and distribution of malnutrition depends on several factors; political and economic situation, education, environment, food pattern, cultural believes, etc. Dalits are the people who are religiously, culturally, socially and economically oppressed, excluded and treated as untouchables; and they belong to different geographical region, language, culture and castes. Therefore, their children are more prone to poor health and various kinds of diseases including malnutrition. So, the present study aimed to assess the prevalence of Protein Energy Malnutrition (PEM) among under-five dalit children and the factors associated with it. Methods: Descriptive cross-sectional study was conducted among 238 under-five dalit children in four selected VDCs of Morang District using cluster sampling technique. Data were collected using interview schedule and anthropometric measurements. Data analysis was done using statistical Package for social sciences (SPSS) version 11.5. Results: Out of 238 children, one-fourth of them belong to age group 12-23 months and more than half (52.9%) were male. The prevalence of PEM was assessed in terms of underweight, stunting and wasting and was found to be 16.8%, 11.3% and 14.7% respectively. Underweight was found to be statistically significant with father’s educational level and antenatal care visit of the mother. Stunting was found to be statistically significant with mother’s occupation and wasting was found to be significant with age of the child, type of family, weaning and distance of the health facility. Conclusion: Prevalence of Protein-energy malnutrition was found to be higher in those children with nuclear family, illiterate parents, poor antenatal care, delayed weaning practices and availability of health facility